Regulation of apoptosis in the immune system - Krammer, Peter H.; Behrmann, Iris; Daniel, Peter; Dhein, Jens; Debatin, Klaus-Michael (Current opinion in immunology, 1994)
Apoptosis in T and B lymphocytes is involved in all fundamental processes in the immune system. It is a mechanism to regulate the course of an immune response and to establish immunological memory as well as central and peripheral tolerance. Apoptosis in lymphocytes is regulated by gene products that induce or block this process. Elucidating the molecular basis for sensitivity and resistance towards induction of apoptosis is the key to the understanding of the development of the immune system, basic immune reactions and the pathogenesis of autoimmune diseases, AIDS and cancer.